Diagnostic Accuracy of the Conners' Adult ADHD Rating Scale in a Postsecondary Population. Issue 14 (December 2019) - Harrison, Allyson G.; Nay, Sylvia; Armstrong, Irene T.
Objective: Clinicians frequently rely upon the results of self-report rating scales when making the diagnosis of ADHD; however, little research exists regarding the ability of self-report measures to accurately differentiate ADHD from other disorders.Method: This present study investigated the ability of the Conners' Adult ADHD Rating Scale (CAARS) to discriminate between 249 postsecondary students with carefully diagnosed ADHD and 507 clinical controls.Results: The overall discriminant validity of the CAARS was 69%, and it had an unacceptably high false positive and false negative rate. At lower prevalence rates, a high score on the CAARS has only a 22% chance of accurately identifying individuals with ADHD.Conclusion: Although the CAARS is an adequate screening measure, it should not be the main method by which a diagnosis is made, as it frequently misidentifies individuals with other psychological complaints as having ADHD. Implications for clinical practice are discussed.